2019
DOI: 10.1021/acsomega.8b03575
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Molecular Details of the Complete Mechanism That Governs the Synthesis of Prostaglandin G2 Catalyzed by Cyclooxygenase-2

Abstract: Cyclooxygenase-2 (COX-2) is the key enzyme involved in the synthesis pathway of prostaglandin G2 (PGG2) by transformation of arachidonic acid (AA). Although COX-2 is one of the principal pharmacological targets by the implication of PGG2 in several human diseases, the classical all-radical mechanism proposed for COX-2 catalysis has never been validated at the molecular level. Herein, molecular dynamics simulations and quantum mechanics/molecular mechanics (QM/MM) calculations were combined to analyze the six s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…A second cyclization involving C8 and C12 generates a bicyclic ring and a radical at C15. Note that the cyclopentane ring is formed in the trans configuration (131). This differs from the non-enzymatically generated isoprostanes which occur predominantly in the cis configuration (132).…”
Section: Catalytic Mechanism Of Coxmentioning
confidence: 93%
“…A second cyclization involving C8 and C12 generates a bicyclic ring and a radical at C15. Note that the cyclopentane ring is formed in the trans configuration (131). This differs from the non-enzymatically generated isoprostanes which occur predominantly in the cis configuration (132).…”
Section: Catalytic Mechanism Of Coxmentioning
confidence: 93%
“…This scenario is the opposite to the case of wild-type COX-2, where the suprafacial and antarafacial oxygen attacks produce the S and R congurations at C 11 , respectively. 13 On the other hand, the potential energy barriers (7.1 to 11.2 kcal mol À1 ) turn out to be small in comparison with that for hydrogen abstraction (24.8 kcal mol À1 ).…”
Section: Qm/mm Calculationsmentioning
confidence: 98%
“…Our calculations conrm the experimental nding by Brash and co-workers, 16 who found that the 8,12-cyclization does not occur in the Gly526Ser mutant COX-2. We know that the cyclopentane ring closure only occurs with a (9R, 11R) conguration, 13,16 but this is just the stereochemical conguration that cannot be reached aer the third mechanistic step in the mutant, as mentioned above. The reason for that can be understood by analyzing Fig.…”
Section: Qm/mm Calculationsmentioning
confidence: 99%
See 2 more Smart Citations